Factors related to the utilization of health services for diabetes mellitus patients during covid 19 pandemic - Sinaga, Martaulina (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Background: The starting point for a healthy life with diabetes is early diagnosis, the longer a person lives with undiagnosed and untreated diabetes, the worse the possible health outcomes. So it is necessary to perform a health check will reduce the risk of complications. This study aims to determine the factors related to the utilization of health services in patients with diabetes mellitus at the Suro District Health Center. Aceh Singkil Year 2020. Methods: This type of research is analytic observational with a cross sectional design. The population was used as a sample, namely all people with Diabetes Mellitus who came for treatment in May 2020 to the Suro Health Center totaling 42 respondents. The data analysis technique used chi square statistical test. Results: Utilization of health services carried out by people with Diabetes Mellitus at the Suro Health Center had a relationship with knowledge with a value of p = 0.006 and perception of pain was related to the use of health services p = 0.009 while distance had no relationship with the use of health services with a value of p = 0.125. Conclusion: Patients with Diabetes Mellitus on average have less knowledge and have negative perceptions about Diabetes Mellitus related to the utilization of health services, innovations to increase knowledge of Diabetes Mellitus and perceptions are recommended specifically for women to continue to use health services to avoid an increase in blood sugar levels first. to prevent complications. Suggestions This research is further carried out for the utilization of health services and policies to design interventions to change the pattern of utilization of health services.